ANALISIS LOGAM BERAT MERKURI (HG) PADA GASTROPODA, LUMPUR DAN AIR DI TELUK AMURANG KABUPATEN MINAHASA SELATAN - Kiwol, Christy (Sam Ratulangi University, 2008)
The purpose of this study is to know the ?Concentration of Heavy Metal Mercury in Gastropods, Sedimentand Sea water at Amurang Bay. As the concentration of these heavy metals in living things (gastropod),sediment, and sea water being figured up that it will be known the level of heavy metal contaminant inAmurang Bay. This study was approached by purposive sampling method and Atomic AbsorptionSpectrophotometer (AAS) of the Laboratory of Balai Riset dan Standarisasi Industri dan Perdagangan(BARISTAND) used to analyze the sample. The result has been showed that the concentration of Mercury(Hg) that found in sea water, sediment and gastropod from Amurang Bay were in the range between 0,04? 0,82 ppm, 19,61 ? 39,63 ppm and 14,67 ? 23,89 respectively. Based on Environment Quality Standardreference the Mercury (Hg) concentration that has been found in this study from Amurang Bay beingunder safety limit level. Keywords : heavy metal, mercury, sea water, sediment, gastropod